Downside of Celebrity Endorsement and Its Effect on Purchasing Pattern of Consumers - Kumar, Vaibhav (2009)
The main motive of the dissertation is to find effect of downside of celebrity endorsements on purchasing pattern of consumer. Today celebrity endorsement is a billion dollar industry, its not only limited to one part of the world. In recent times it has spread its wings all over the world. It has gained tremendous amount of popularity. With popularity comes many negative aspects of celebrity endorsement which is spoiling the party. There has been overdose of this phenomenon people are getting bored of it. It is losing its popularity among consumers.